UNIT 3.44 Labeling and Magnetic Resonance Imaging of Exosomes Isolated from Adipose Stem Cells. Issue 1 (19th June 2017) - Busato, Alice; Bonafede, Roberta; Bontempi, Pietro; Scambi, Ilaria; Schiaffino, Lorenzo; Benati, Donatella; Malatesta, Manuela; Sbarbati, Andrea; Marzola, Pasquina; Mariotti, Raffaella
Abstract : Adipose stem cells (ASC) represent a promising therapeutic approach for neurodegenerative diseases. Most biological effects of ASC are probably mediated by extracellular vesicles, such as exosomes, which influence the surrounding cells. Current development of exosome therapies requires efficient and noninvasive methods to localize, monitor, and track the exosomes. Among imaging methods used for this purpose, magnetic resonance imaging (MRI) has advantages: high spatial resolution, rapid in vivo acquisition, and radiation‐free operation. To be detectable with MRI, exosomes must be labeled with MR contrast agents, such as ultra‐small superparamagnetic iron oxide nanoparticles (USPIO). Here, we set up an innovative approach for exosome labeling that preserves their morphology and physiological characteristics. We show that by labeling ASC with USPIO before extraction of nanovesicles, the isolated exosomes retain nanoparticles and can be visualized by MRI. The current work aims at validating this novel USPIO‐based exosome labeling method by monitoring the efficiency of the labeling with MRI both in ASC and in exosomes. © 2017 by John Wiley & Sons, Inc.